2003
DOI: 10.1177/108201303036093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Treatment on the Antioxidant Activity and Content of Carotenoids and Phenolic Compounds of Cactus Pear Cladodes (Opuntia ficus-indica)

Abstract: Cactus pears (Opuntia ficus-indica) are draught resistant plants originated in Mexico. Their flattened stem segments, called cladodes, have moisture, protein and fibre contents of 92, 1-2 and 4-6% respectively, and a pectin content in the range of 0.8-3.3% depending on the species. They also contain certain concentration of carotenoids which are of special interest because of their antioxidant activity. This work is aimed to identify and quantify the main carotenoids present in the stems and to evaluate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
60
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 34 publications
11
60
2
Order By: Relevance
“…Total vitamin C (ascorbic and dehydroascorbic acid) in 100 g fresh weight amounted up to 22 mg, b-carotene to 11.3 -53.5 lg, thiamine to 0.14 mg, riboflavin to 0.6 mg, and niacine to 0.46 mg, respectively [20,22,29,66,67] ( [44] of fresh cactus pear cladodes determined the presence of acryptoxanthin (20%), b-carotene (36%), and lutein (44%) amounting to 229 lg/g dry weight altogether with increasing amounts upon thermal treatment [68]. While lutein is typical for green vegetables [69 -72], no information is yet available on folate in cactus usually accompanying chlorophyll in green vegetable tissues such as in spinach, lettuce or Swiss chard [73,74].…”
Section: Vitamins Carotenoids and Chlorophyllsmentioning
confidence: 99%
“…Total vitamin C (ascorbic and dehydroascorbic acid) in 100 g fresh weight amounted up to 22 mg, b-carotene to 11.3 -53.5 lg, thiamine to 0.14 mg, riboflavin to 0.6 mg, and niacine to 0.46 mg, respectively [20,22,29,66,67] ( [44] of fresh cactus pear cladodes determined the presence of acryptoxanthin (20%), b-carotene (36%), and lutein (44%) amounting to 229 lg/g dry weight altogether with increasing amounts upon thermal treatment [68]. While lutein is typical for green vegetables [69 -72], no information is yet available on folate in cactus usually accompanying chlorophyll in green vegetable tissues such as in spinach, lettuce or Swiss chard [73,74].…”
Section: Vitamins Carotenoids and Chlorophyllsmentioning
confidence: 99%
“…Thermal treatments increased the extractability of these pigments and the antioxidant activity was related to the carotenoid concentration. Total phenolic content decreased after the thermal treatments; however this result had little effect on the antioxidant activity (Jaramillo et al 2003). A study revealed that both antioxidative and DNA damage-reduction activities are increased with increasing cactus pear fruits extract (CPFE).…”
Section: Medicinal Usesmentioning
confidence: 99%
“…The total phenolic compounds (TPC) were determined in the ethanolic extract, according to the Folin-Ciocalteu method (Jaramillo-Flores et al, 2003) by using a spectrophotometer (6505 UV/Vis, Jenway Ltd., Felsted, Dunmow, UK), and gallic acid was used to prepare the calibration curve. The antioxidant activity of LCP and burger samples was determined by the (DPPH) method (Lee et al, 2003).…”
Section: Proximate Analysismentioning
confidence: 99%